2015
DOI: 10.1136/heartjnl-2014-305730
|View full text |Cite
|
Sign up to set email alerts
|

Survival in South Asian and White European patients after acute myocardial infarction

Abstract: When adjusted for differing prevalence of cardiovascular risk factors in the two ethnic groups, survival following AMI was similar for SA and WE patients in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…There are important differences between Asians and Caucasians in cardiovascular disease risk factors, incidence, and survival . Asians have a higher prevalence of risk factors such as diabetes, hypertension, renal insufficiency, and narrower coronary arteries . These risk factors differentially affect left ventricular function between these two races .…”
Section: Introductionmentioning
confidence: 99%
“…There are important differences between Asians and Caucasians in cardiovascular disease risk factors, incidence, and survival . Asians have a higher prevalence of risk factors such as diabetes, hypertension, renal insufficiency, and narrower coronary arteries . These risk factors differentially affect left ventricular function between these two races .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease incidence rates are higher in South Asians in our locality compared with whites 19. Further, cardiovascular disease risk factors are more prevalent in South Asians compared with white patients, with the exception of smoking 19–21.…”
Section: Discussionmentioning
confidence: 66%
“…In the county of Leicestershire, individuals of South Asian ethnicity constitute approximately 15% of the population. We have reported higher incidence rates of coronary artery disease19 and heart failure20 21 in the Leicestershire South Asian population compared with Caucasian patients, but similar19 20 or better21 case fatality. In this study, we aimed to use this enriched population with a high density of individuals of South Asian ethnicity to determine whether risk of bradycardias differ between South Asians and Caucasians by comparing PPM implantation rates in these two ethnic groups.…”
Section: Introductionmentioning
confidence: 68%
“…Over the years, epidemiological studies from several countries including Canada 2–4 , South Africa 5 and the UK 6–8 have shown that individuals of South Asian ethnicity are at higher risk for coronary heart disease and mortality compared with other ethnicities. Coronary heart disease develops at a younger age in migrant South Asian populations compared with indigenous populations: compared with white Europeans, South Asians admitted with a myocardial infarction were younger by approximately 5 years and had a higher prevalence of cardiovascular risk factors, including diabetes 9 .…”
Section: Introductionmentioning
confidence: 99%